Suplementasi Jus Daun Pegagan dan Limbah Wortel terhadap Produktivitas Puyuh Jantan (Cortunix cortunix japonica) - H Ariqoh; S Prayoga; B S Hermanto; W Hermana (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2019)
The purpose of this study was to compare commercial vitamin supplements to natural vitamins derived from pegagan leaves and carrot waste on drinking water. This experiment was designed as a completely randomized design with 5 treatments and 3 replicates; Control was drinking water without supplements (P1), drinking water with supplementation of commercial vitamin (P2), drinking water with carrot waste and pegagan leaves juice 5% (P3) , 10% (P4) and 15% (P4) tested to 150 male quails that were reared up to 3 months. The variables observed were performance of male quail that includes feed consumption, body weight gain, feed conversion ratio, initial weight, final body weight, carcass weight, and level of MDA (Malonaldehyde) quail meat. The results of this study showed the treatments of addition supplement have no significant effect on quail performance (feed consumption, weight gain, feed conversion ratio, initial weight, final body weight, carcass weight), but the treatment of 5% pegagan leaves juice and carrot waste significantly increased level of MDA quail meat 55.652 % compared to control. It is concluded that supplementation of pegagan leaves and carrot waste in drinking can increase MDA of quail meat. Keywords: carrot waste, juice supplement, male quail, Malonaldehyde, pegagan leaves